Dendrimers as Modifiers of Inorganic Nanoparticles for Therapeutic Delivery in Cancer - Mkhuseli Zenze; Aliscia Daniels; Moganavelli Singh (MDPI AG, 2023)
The formulation of nanoscale systems with well-defined sizes and shapes is of great interest in applications such as drug and gene delivery, diagnostics and imaging. Dendrimers are polymers that have attracted interest due to their size, shape, branching length, amine density, and surface functionalities. These unique characteristics of dendrimers set them apart from other polymers, their ability to modify nanoparticles (NPs) for biomedical applications. Dendrimers are spherical with multiple layers over their central core, each representing a generation. Their amphiphilic nature and hollow structure allow for the incorporation of multiple drugs or genes, in addition to enabling easy surface modification with cellular receptor-targeting moieties to ensure site-specific delivery of therapeutics. Dendrimers are employed in chemotherapeutic applications for the delivery of anticancer drugs. There are many inorganic NPs currently being investigated for cancer therapy, each with their own unique biological, chemical, and physical properties. To favor biomedical applications, inorganic NPs require suitable polymers to ensure stability, biodegradability and target specificity. The success of dendrimers is dependent on their unique structure, good bioavailability and stability. In this review, we describe the properties of dendrimers and their use as modifiers of inorganic NPs for enhanced therapeutic delivery. Herein, we review the significant developments in this area from 2015 to 2022. Databases including Web of Science, Scopus, Google Scholar, Science Direct, BioMed Central (BMC), and PubMed were searched for articles using dendrimers, inorganic nanoparticles and cancer as keywords.